FENOMENOLOGI PEMASARAN ERA DIGITAL DALAM GENERASI MILENIAL PADA PRODUK INDIHOME (Studi Pada PT. Telekomunikasi Indonesia, Tbk Divre I Medan) - Novianta, Novianta; Siregar, Onan Marakali (Transpublika Publisher, 2023)
At this time many business people use digital as their marketing activities, including PT. Telekomunikasi Indonesia, Tbk conducts digital marketing on milennial generation in marketing Indihome products through social media so that the writer is interested in conducting research in this phenomenology. This study aims to determine the marketing of the digital era in milennial generation of indihome products at PT. Telekomunikasi Indonesia, Tbk Divre I Medan. Digital era marketing is focused through social media such as Instagram, Facebook, Twitter and others that focus on millennial generation. The form of this research uses a descriptive method with a qualitative approach with the intention of describing events or facts contained in an object of research by conducting interviews and observations then analyzing the data obtained from the research location and comparing with theories. From this study it can be concluded that overall the phenomenology of marketing in the digital era in milennial generation of Indihome products implemented by PT. Telekomunikasi Indonesia, Tbk Divre I Medan has taken place where marketing is done through digital like on social media facebook, instagram, OLX, youtube. Marketing content on Instagram with the name (@IndiHome) and Facebook with the name (IndiHome) by using interesting images as done with celebrities, artists, influencers and promos which are done through feeds and stories on Instagram and Facebook. Youtube content with Bayu Prabowo's video titled Indihome 2P Review (Internet + TV).